Design and training of rice thresher machines for the farming group communities in Besar II Terjun Village - Ahmad Yunus Nasution; Tulus Burhanuddin Sitorus; Tania Alda; Gabriel Alexandro Sembiring; Joi Jogi Pakpahan; Siti Qeisya Puandhani Siregar; Muhammad Ibrahim Syah; Muhammad Reihan Triandhika (Journal of Community Service in Science and Engineering (JoCSE), 2023)
Most of the Besar II Terjun Village residents live in agriculture. So far, people still use conventional methods to separate rice by hitting the harvested rice. In this community service activity, a rice threshing machine was designed. The rice thresher machine has power = 5.5 HP with engine type = Air Cooled 4 Stroke OHV Single Cylinder; maximum torque = 1.1 Kg.m / 3600 rpm; and maximum output = 4 KW / 4000 rpm. This machine has a capacity of 300 kg/minute. This community service activity aims to help the Sukapura Village community maximize its potential and provide insight for SMEs regarding effectiveness, efficiency, productivity, and safety in carrying out the catfish production process. The methods used include observation methods to determine the needs of SMEs for processed catfish food, design methods, presentation methods, and discussion methods as a form of assistance in starting a catfish product processing business. Sebagian besar penduduk Desa Besar II Terjun mempunyai mata pencaharian di bidang pertanian. Selama ini masyarakat masih menggunakan cara konvensional dalam melakukan pemisahan padi,yaitu dengan memukul padi yang dipanen. Pada kegiatan pengabdian masyarakat ini dilakukan perancangan mesin perontok padi.  Mesin perontok padi yang dirancang memiliki daya = 5,5 HP; dengan tipe mesin = Air Cooled 4 Tak OHV Single Cylinder; torsi maksimum = 1,1 Kg.m / 3600 rpm; dan putput maksimum = 4 KW / 4000 rpm. Mesin ini memiliki kapasitas 300 kg/menit. Kegiatan pengabdian masyarakat ini bertujuan untuk membantu masyarakat Desa Sukapura dalam memaksimalkan potensi yang ada dan memberikan wawasan bagi pelaku UKM mengenai efektivitas, efisiensi, produktivitas, serta keselamatan dalam melakukan proses produksi olahan lele. Metode yang dilakukan antara lain, metode observasi untuk mengetahui kebutuhan UKM makanan olahan lele, metode perancangan, metode presentasi, dan metode diskusi sebagai bentuk pendampingan dalam merintis usaha olahan produk lele.